Efektivitas Edukasi terhadap Pengetahuan dan Sikap Pegawai Dalam Penerapan Keamanan Pangan: Studi Pre-Test Post-Test pada Siswa Tata Boga yang Bertugas di Restoran Sekolah X Kabupaten Karawang - Rahmawati, Lia; Fikri, Al Mukhlas; Kurniasari, Ratih (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Food safety is an essential aspect of the restaurant industry, which heavily relies on employees’ knowledge and attitudes in implementing proper procedures. Awareness of food safety not only influences the quality of the food served but also affects consumer health and the restaurant’s reputation. This study aims to evaluate the effectiveness of three educational media—2D posters, 3D animated videos, and applicative media (Food Safety Puzzle)—in improving the knowledge and attitudes of restaurant employees, who in this case are culinary students on duty at the restaurant, regarding food safety. The method used was an experimental design with Wilcoxon Signed Rank Test analysis to assess changes in respondents’ knowledge and attitudes before and after the educational intervention. The results showed that all educational media successfully improved employees’ knowledge significantly. Specifically, 100% of respondents achieved an “Excellent” level of knowledge after using the 2D poster. Additionally, the applicative media (Food Safety Puzzle) had the greatest impact on attitudes, with 60% of respondents reaching the “Excellent” category after the educational session. In conclusion, a multifaceted approach in delivering food safety education proved effective in enhancing the knowledge and attitudes of restaurant employees. Therefore, it is recommended that restaurants implement various educational media in their training programs. Further research is also needed to explore the long-term effects of food safety education programs to ensure that employees consistently apply the knowledge gained in their daily practices.